A wearable device to monitor ocular comfort. Issue 5 (October 2019) - Read, Michael L.; Morgan, Philip B.; Maldonado-Codina, Carole
Highlights: A wearable electronic logger was developed to track episodes of lens awareness during contact lens wear. 40 subjects wore their habitual contact lenses and logged episodes of lens awareness by pressing the electronic logger. Awareness events were more frequent after lens application (lens settling) and before lens removal (end-of-day discomfort). Symptomatic lens wearers experienced a greater proportion of awareness events in the second half of the wear period. This device is likely to be a key tool to further understanding of lens-associated discomfort and dry eye disease. Abstract: Purpose: To develop and evaluate a wearable device (the lens awareness logger, LAL) to record subjective lens awareness during contact lens wear. Methods: The LAL is a compact electronic event-logging device incorporating a tactile switch and belt-clip. Forty contact lens wearers (20 symptomatic and 20 asymptomatic) took part in a clinical evaluation of the LAL device. Subjects were instructed to wear their habitual soft contact lenses for 2 days (>8 h wear) and use the LAL device. Subjects activated the LAL device immediately prior to lens application and deactivated it following lens removal. If a subject became aware of their contact lenses at any point throughout the wear period they were instructed to depress the button on the LAL device. Results: The mean number of lens awareness events per hour was 1.3, although there was substantial variation between subjects (standard deviation 1.4). The distribution of lens awareness events throughout the contact lens wearing period showed significantly elevated awareness following lens application and prior to lens removal (p < 0.0001). In addition, symptomatic subjects had a statistically higher percentage of LAL events in the second half of the lens-wearing day compared with asymptomatic subjects (p = 0.02). The LAL findings for each subject appear consistent across the two days (i.e. no fatigue or learning effect). The LAL device was well accepted by subjects with 38 of the 40 subjects reporting it was either 'very easy' or 'fairly easy' to use. Conclusion: The LAL device was able to monitor ocular comfort throughout a period of contact lens wear and was well accepted by subjects. The ability of the LAL device to track ocular awareness events through the day, with high temporal resolution, means it is likely to be a key tool to further understanding of contact lens associated discomfort and dry eye disease.